Thermal signatures of liquid droplets on a skin induced by emotional sweating. Issue 2 (15th March 2022) - Koroteeva, E. Yu.; Bashkatov, A. A.
ABSTRACT: As a result of physiological thermoregulation, human eccrine sweat glands produce sessile droplets on the skin. This paper studies the thermal signatures associated with droplet dynamics on the face and the fingers of an individual using a mid-wave infrared camera. The thermal image analysis focuses on the morphology and evolution of individual droplets induced by various emotional stimuli. We follow the growth and evaporation rate of droplets with different lifetimes ranging from seconds to tens of seconds. The results are of interest in the fields of medicine and psychophysiology (in the studies of human emotional sweating) or physics (for the development of models of evaporative surface cooling).